Screening of two Sesbania species for fodder potential and response to phosphorus application on an acid soil in Ethiopia - Siaw, D.E.K.A.; Berhe, Kahsay; Tothill, J.C. (International Livestock Centre for Africa, 1993)
Sesbania sesban and S. goetzei accessions were screened on Vertisols at PH 6.8 and acid clay soils (Nitosols) with and without application of phosphours (60 kg P/ha). Both species were generally well adapted to the Vertisols and grew to an overall mean height of 249 cm 14 months after transplanting. On Nitosols however, only S. sesban performed well. S. goetzei produced very low dry-matter yields. S. sesban outperformed S. goetzei in leaf and stem production as well as in trunk diameter. Significant increases were recorded in these three parameters in both species as a result of phosphorus application. The nitrogen content of leaves was high and generally exceeded 4 percent. In vitro dry-matter digestibility (IVDMD) was also high, with values in excess of 70 percent for most accessions. Insoluble proanthocyanidin content varied widely (from 10 to 59), the lower values were low, ranging from 13 to 22 percent. Mineral element (P.K. and Ca) contents were adequate for livestock feeding as they were higher than recommended dietary levels.